ASS-Intoleranz-Syndrom und persistierende Rhinosinusitis: Differentialdiagnostik und Therapie = ASA-intolerance syndrome and persistent rhinosinusitis - Kirsche, Hanspeter; Klimek, Ludger (HNO, 2015)
Background: A differential diagnosis of persistent chronic rhinosinusitis is ASA-intolerance syndrome (AIS), also known as Aspirin®‑exacerbated respiratory disease (AERD), Samter-Trias (Samter’s disease, Morbus Widal). Particularly in cases of frequent recurrency of nasal polyps in combination with bronchial asthma and hypersensitivity reactions to acetylsalicylic acid (ASA) and other nonsteroidal anti-inflammatory drugs (NSAR) can often be referred to an underlying AIS. The pathogenesis of this syndrome is attributed to a misallocation of the arachidonic acid metabolism, resulting in an increased leukotriene production. Methods: The diagnosis may be difficult in the early stages of the disease with incomplete triad of symptoms. Results: Therapy may consist of paranasal sinuses surgery, drug therapy and adaptive deactivation as the only causal treatment option for patients with AIS. Conclusion: For adaptive desactivation, positive effects were actually shown even in patients with long-term recurrent or persistent complaints of chronic rhinosinusitis.